Between Land and a Raised Foot: Thania Petersen Stands Her Ground. - Simbao, Ruth (Art Journal)
A close connection between the earth and our feet can be deeply spiritual, powerfully transformational, and potentially subversive. In 2017, I developed the phrase, "between land and a raised foot" that explores the transitional space between a poised foot and the earth beneath it. I draw from the psychoanalytic notion of potential space, Buddhist practices of walking meditation, and African practices of associating land with ancestral spirits. In psychoanalysis, potential space is painful, yet creative and generative. More broadly, this space between land and a raised foot opens up possibilities of resistance and healing. Focusing on the work of contemporary artist Thania Petersen, I situate this phrase in the context of South Africa, where a raised foot is sometimes associated with the gesture of a raised fist, and where land remains contentious. Petersen's artwork grapples with the history of displacement of Cape Muslim (also known as Cape Creole) people in Cape Town, who were formerly labelled "Cape Malay." Through various satirical strategies that involve standing, sitting, lying, or walking on land, she challenges the colonial "Cape Malay" trope of docile people. Often employing her own body, Petersen registers resistance and deliberately performs disobedient acts. She walks the "wrong" way, steps over graves, alludes to protest marches, and defiantly occupies space with her bodily presence. Challenging global attempts to control sacred sites through tourism as well as right-wing conservatism and dogma, Petersen ignites protest. It is through this anger that she is able to develop processes of mourning and healing with the land.